EPR and electrochemical quantification of oxygen using newly synthesized para-silylated triarylmethyl radicals. (March 2015) - Boutier-Pischon, A.; Auger, F.; Noël, J.-M.; Almario, A.; Frapart, Y.-M.
Abstract: Novel silylated triarylmethyl (TAM) radicals based on TAM core CT-03 and their electron paramagnetic resonance (EPR) spectra are evaluated as a function of oxygen concentration. Combination of peak-to-peak linewidth of the EPR signal and electrochemical determination allows designing a method for oxygen quantification in phosphate buffer, dimethylsulfoxide, and dichloromethane, which can be extended to other solvents.